Improvement of Designing Laboratory Scale Plastic Chopping Equipment with the TRIZ Method (Theorija Rezhenija Izobretatelskih Zadach) - Fijra, Rafiqa; Saleh , Zulkiffli; Rifqi Adinugraha , M.; Hastarina, Merisha; Wahyudi, Bayu (International Journal of Science, Technology & Management, 2022)
The practical use of plastic increasing the demand for plastic. Plastic waste is difficult to decompose, currently many efforts have been made to reduce this plastic waste. A plastic chopping machine is a tool used to produce shredded plastic items into small pieces of a certain size, which can later be used for further processing as a recycling effort. This study improves the design of an existing plastic chopper that focuses on increasing reliability and convenience by the user. The analysis was carried out using a fishbone diagram and the TRIZ design method. The research resulted in a number of causes for the emergence of problems in the operation of the plastic chopper and a new design for the tool, namely improvements in terms of the type of blade, type of motor, and size of the tool. Keywords: Improvement designing, plastic chopper, fishbone diagram, and TRIZ method.